Answer:
The equation in slope-intercept form:
Step-by-step explanation:
Given the point
We know that the slope-intercept form of the line equation is
[tex]y=mx+b[/tex]
where m is the slope and b is the y-intercept.
substituting the values m=1 and the point (-8, -6) to determine the y-intercept i.e. 'b'.
[tex]y=mx+b[/tex]
-6 = 1(-8)+b
-6 = -8 + b
b = -6+8
b = 2
Now, substituting the values m=1 and the b = 2 to determine the line equation in slope-intercept form
[tex]y=mx+b[/tex]
[tex]y = 1(x) + 2[/tex]
[tex]y = x+2[/tex]